2015
DOI: 10.1089/scd.2014.0152
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Propagation of Neural Crest Stem Cells from Mouse Embryonic Stem Cells via Cranial Neurospheres

Abstract: The developmental fate of the multipotent neural crest (NC) is determined along with the neural axis in which NC cells are generated. Only the cranial NC can differentiate into mesectodermal derivatives such as osteoblasts, chondrocytes, and adipocytes in vivo. Here, we attempted to selectively differentiate mouse embryonic stem (ES) cells into cranial NC stem cells and propagate them to explore their developmental potential to differentiate into mesectodermal derivatives. Using aggregation cultures in feeder-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Another study has found that a small neurosphere size is associated with efficient neuralization of ES cells (5). In contrast, large neurosphere size contributes to suppression of ES cell neuralization and promotes mesoderm differentiation (38). Further study is needed to determine whether larger neurosphere size would provide an advantage for NCC differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…Another study has found that a small neurosphere size is associated with efficient neuralization of ES cells (5). In contrast, large neurosphere size contributes to suppression of ES cell neuralization and promotes mesoderm differentiation (38). Further study is needed to determine whether larger neurosphere size would provide an advantage for NCC differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we derived cells from miPS which are closely migratory cNCCs genes. Previously, NCCs have been derived from ES or iPS cells using various approaches [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110], and the protocol used in the present study was based on the methods outlined by Bajpai et al [23]; however, few studies have investigated changes in the properties of cNCCs at different time points after induction.…”
Section: Discussionmentioning
confidence: 99%
“…The NTE differentiation was performed according to published protocols (Wang et al., 2011) and the NCC differentiation was performed according to a published protocol (Minamino et al., 2015). For additional details, see Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro , ESCs can differentiate into NTE cells (Watanabe et al., 2005, Zhang, 2006) and NCCs (Lee et al., 2007, Liu et al., 2012, Minamino et al., 2015). Therefore, ESCs are an excellent model for the study of early development of the nervous system and the regulatory mechanisms that determine the differentiation of NTE cells and NCCs.…”
Section: Introductionmentioning
confidence: 99%